2021
DOI: 10.3390/ijerph18199953
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Quality of Nursing Work Life and Uniformed Nurses’ Attitudes and Practices Related to COVID-19 in the Philippines: A Cross-Sectional Study

Abstract: (1) Background: Coronavirus disease 2019 (COVID-19) has spread rapidly worldwide. Uniformed nurses have played a critical role during the COVID-19 pandemic in the Philippines; however, uptake of literature is limited. This study assessed the relationship between quality of nursing work life (QNWL) and nurses’ attitudes and practices during the COVID-19 pandemic. (2) Methods: A descriptive cross-sectional design was used. Participants were recruited from four government hospitals in the Manila metropolitan area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…(37) Research in Iran and Ethiopia highlighted the need for interventions to improve a work quality of life considered low. (38,39) The coronavirus pandemic has intensified the stressful working conditions for nursing professionals, negatively influencing their perception of work quality of life and altering their performance. Factors such as workload, managerial support, and intrinsic motivation play a crucial role in this perception.…”
Section: Discussionmentioning
confidence: 99%
“…(37) Research in Iran and Ethiopia highlighted the need for interventions to improve a work quality of life considered low. (38,39) The coronavirus pandemic has intensified the stressful working conditions for nursing professionals, negatively influencing their perception of work quality of life and altering their performance. Factors such as workload, managerial support, and intrinsic motivation play a crucial role in this perception.…”
Section: Discussionmentioning
confidence: 99%
“…En relación a la CVT, los resultados muestran que el puntaje fue significativamente bajo, lo que pone en riesgo de desequilibrio la CVT de las/os enfermeras/os de tres hospitales públicos de Ecuador, pudiendo influir en su propia salud, como en la calidad del cuidado e institución. El resultado encontrado en esta investigación, difiere de otros, donde se han encontrado niveles de et al, 2016;Navales et al, 2021).…”
Section: Discussionunclassified
“…Among the ten studies included in this review, one is from Philippines. Navales et al (2021), one is from Occupied Palestinian Territory (oPt) (Shawahna, 2021a), one is from Nigeria Ejeh et al (2020), one is from Saudi Arabia (Temsah et al, 2021), others two from Ethiopia Tadesse et al (2020); Feleke et al (2021), one is from India Mahato & Suryavanshi (2020), one is from Uganda Olum et al (2020), one is from China Wen et al (2021) and one is from Lebanon (Saadeh et al, 2021). Overall, most study indicated that nursing staff KAP scored well.…”
Section: Demographic Characteristic For Nursesmentioning
confidence: 97%